Steroidal scaffold decorations in Solanum alkaloid biosynthesis - Lucier, Rosalind; Kamileen, Mohamed O.; Nakamura, Yoko; Serediuk, Sofiia; Barbole, Ranjit; Wurlitzer, Jens; Kunert, Maritta; Heinicke, Sarah; O'Connor, Sarah E.; Sonawane, Prashant D. (Molecular Plant, 2024)
Steroidal glycoalkaloids (SGAs) are specialized metabolites produced by hundreds of Solanum species, including important vegetable crops such as tomato, potato, and eggplant. Although it has been known that SGAs play important roles in defense in plants and ``anti-nutritional''effects (e.g., toxicity and bitterness) to humans, many of these molecules have documented anti-cancer, anti-microbial, antiinflammatory, anti-viral, and anti-pyretic activities. Among these, a-solasonine and a-solamargine isolated from black nightshade (Solanum nigrum) are reported to have potent anti-tumor, anti-proliferative, and anti-inflammatory activities. Notably, a-solasonine and a-solamargine, along with the core steroidal aglycone solasodine, are the most widespread SGAs produced among the Solanum plants. However, it is still unknown how plants synthesize these bioactive steroidal molecules. Through comparative metabolomictranscriptome-guided approach, biosynthetic logic, combinatorial expression in Nicotiana benthamiana, and functional recombinant enzyme assays, here we report the discovery of 12 enzymes from S. nigrum that converts the starting cholesterol precursor to solasodine aglycone, and the downstream a-solasonine, a-solamargine, and malonyl-solamargine SGA products. We further identified six enzymes from cultivated eggplant that catalyze the production of a-solasonine, a-solamargine, and malonyl-solamargine SGAs from solasodine aglycone via glycosylation and atypical malonylation decorations. Our work provides the gene tool box and platform for engineering the production of high-value, steroidal bioactive molecules in heterologous hosts using synthetic biology.
Keywords: a-solamargine; Biosynthetic pathway; malonyl-solamargine; Solanum; Specialized metabolites; steroidal glycoalkaloids